If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -17 = -7 + p Reorder the terms: -17 + 3p = -7 + p Solving -17 + 3p = -7 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -17 + 3p + -1p = -7 + p + -1p Combine like terms: 3p + -1p = 2p -17 + 2p = -7 + p + -1p Combine like terms: p + -1p = 0 -17 + 2p = -7 + 0 -17 + 2p = -7 Add '17' to each side of the equation. -17 + 17 + 2p = -7 + 17 Combine like terms: -17 + 17 = 0 0 + 2p = -7 + 17 2p = -7 + 17 Combine like terms: -7 + 17 = 10 2p = 10 Divide each side by '2'. p = 5 Simplifying p = 5
| 36-25/5+3*3= | | 36-25/5+3*3=40 | | 8+x*3-1=62 | | -9s=6 | | s(t)=-16t^2+44t+4 | | 4x-2(x-4)=-5+4x+7 | | z=m^2-m(1-i)-3(2+i) | | 45x^2-7x-12=0 | | 0.006w=-0.54 | | x+1.23=65.50 | | 5t-15=2t | | 5a-3(2p+3)= | | -4.9=7m | | 14x=189-7x | | 5x+11=-59 | | 6y^2-54y=-12 | | -4x+12=-6x-36 | | 3x+2x=4x-4 | | 30=k+18 | | 4+3n-77=0 | | 208x=-4 | | 36x^2-4y^2=0 | | 2c-1=1 | | 2ln(5x)-ln(2x)=2.5 | | a-5=21 | | 5(d-15)=90 | | -8x=x^2+15 | | 8a+4-7a=3 | | p+6=28 | | y=3x^4-4X^3-12 | | 1.6r=80 | | 3.5h=x |